1995
DOI: 10.1080/00049539508257518
|View full text |Cite
|
Sign up to set email alerts
|

Testing kinaesthetic acuity in preschool children

Abstract: Attempts to dauibc the kinatstbctic d e v d o p n t of young children have ban limited by the use of trdo which ue desigocd for OldalAldrm dinappropnrte ' fortutingthoseofprrJchoolage.Atask r m~~c of I 3to Qyar-old group compared with that of a 5 to dycar-old p u p . The task involved a passive hnd movement to 1 of 16 positions With the hand hidden from the child's view, tlle child identifying the position to which tbeirhnnd had kxn moved by 8 vabal nsponse (naming the aaimal picrund at that loution). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Only two studies appear to have examined kinaesthetic acuity, and they have provided contrary results. Using the KAT (Livesey & Parkes, 1995), Whitmont and Clark (1996) found significantly poorer kinaesthetic acuity and poorer fine motor control in children with ADHD compared with control children. In contrast, we found no significant differences in kinaesthetic acuity between children with either ADHD-PI or ADHD-C and control children (Piek, Pitcher & Hay, 1999).…”
Section: Can Sensory-motor Deficits Distinguish Adhd From Dcd?mentioning
confidence: 96%
See 1 more Smart Citation
“…Only two studies appear to have examined kinaesthetic acuity, and they have provided contrary results. Using the KAT (Livesey & Parkes, 1995), Whitmont and Clark (1996) found significantly poorer kinaesthetic acuity and poorer fine motor control in children with ADHD compared with control children. In contrast, we found no significant differences in kinaesthetic acuity between children with either ADHD-PI or ADHD-C and control children (Piek, Pitcher & Hay, 1999).…”
Section: Can Sensory-motor Deficits Distinguish Adhd From Dcd?mentioning
confidence: 96%
“…Complex visuospatial processing was investigated using the subtests of Block Design, Object 7 Assembly and Geometric Design from the Wechsler Preschool and Primary Scale of Intelligence-Revised (WPPSI-R: Wechsler, 1989). In addition, kinaesthetic acuity was tested using the Kinaesthetic Acuity Test (KAT: Livesey & Parkes, 1995). This involves passive movement of the child's hand in the horizontal plane from the centre of a circle to one of 16 equally spaced targets (animal stickers).…”
Section: Sensory-motor Deficits and Dcdmentioning
confidence: 99%
“…The results from a series of studies that used the KAT (Coleman, Piek, & Livesey, 2001;Livesey & Coleman, 1998;Livesey & Intili, 1996;Livesey & Parkes, 1995) supported the view that previous measures had underestimated children's ability. Threeyear-olds were shown to be kinesthetically competent, there was significant improvement in kinesthetic acuity across the preschool years, and it was also shown that there is a significant relationship between performance on the KAT and on tests of motor ability.…”
mentioning
confidence: 81%
“…There is some evidence that visual–kinesthetic sensory integration occurs by 8 years of age (Chicoine et al, 1992; Manyam & Laszlo, 1989). Investigations of early kinesthetic development (Livesey & Coleman, 1998; Livesey & Intili, 1996; Livesey & Parkes, 1995) have further indicated that such sensory integration is likely to be developing in the preschool years. Lautrey and Chartier (1991) proposed that, in parallel with the emergence of sensory integration, kinetic imagery emerges between the ages of 5 and 7 years.…”
mentioning
confidence: 99%
“…Testing of proprioceptive ability, however, remains di cult, as there are very few objective tools to measure proprioception. Previous studies estimated proprioception using a kinesthetic sensitivity test (KST) [35] and kinesthetic acuity test (KAT) [47] in children with [36,37] and without [35,37,48] DCD, but the accuracy of these methods have been criticized [45,49]. Joint position sense is a simpler method than measuring movement sense [11], and a variety of tools, including goniometers [41] and other customized apparatuses [7,9,11,49], have been used, however, mainly to assess proprioception of the upper extremity.…”
Section: Introductionmentioning
confidence: 99%